The relationship between well-being and quality of life (QoL): The case study of urban middle income (M40) civil servant in Public Service Department (PSD), Putrajaya / Najhatul Alliyyah Ramzi - Ramzi, Najhatul Alliyyah (2019)
Due to the increasing cost of living and downfall of Malaysian Ringgit value, the quality of life (QoL) of Malaysians have been affected tremendously. Those who are staying in urban areas are more pressured by this economic condition. The government had implemented numerous programs for the public to help reduce their financial burden. One of the main highlights of the Eleventh Malaysia Plan (MP-11) emphasised that the middle income (M40) would earn a household income minimum of RM8,960. The majority of the M40 group is civil servants. Their remuneration scheme did not depends on market value but determined by their grade. This caused inequality between rural and urban civil servants as they received the same amount of remuneration since they are in the same job grade, as those in the rural areas do not have the concerns for economic factors faced by urban M40 civil servant. Hence, the main aim of this paper is to analyse Quality of Life (QoL) of urban M40 civil servant who lives in the city. It discusses the concept of QoL and review the factors affecting QoL among urban M40 civil servant. Using quantitative approach, 217 questionnaires were distributed in Public Service Department (PSD), Putrajaya among M40 officers. The findings showed the level of QoL among urban M40 civil servant was satisfactory with mean value 5.16. It was determined by referring to Diener et al. (1993) scale. At the same time, it showed that well-being index have a correlation with QoL among urban M40 civil servant after implementation of Pearson correlation test. Among all well-being indicators, the most influential factors towards QoL was family under social well-being with β=0.3 above others. In conclusion, in order to improve the QoL among urban M40 civil servant, economic factors should not be the sole factor, as social well-being is also an important aspect to determine the QoL of individuals among urban M40 civil servant.